High-temperature-resistant structural bearing-wave transmission integrated composite material and preparation method thereof
Through the method of co-curing integrated molding, a high-temperature resistant composite material composed of structural bearing area, transition area and wave-transmitting area is used to solve the problems of low interfacial layering and interlayer shear strength in existing materials, achieving the effects of short preparation period, low cost and excellent performance.
Patent Information
- Application Number
- CN202311081387.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-25
- Publication Date
- 2025-02-25
AI Technical Summary
The existing high-temperature-resistant structure bearing-wave-transmissive composite materials have interfacial layering and low interlayer shear strength during the preparation process, resulting in long preparation cycle, high production cost and low reliability.
A high-temperature resistant structural bearing-wave-transmissive integrated composite material is adopted. Through the method of co-curing integrated molding, the material consists of the structure bearing area, the transition area and the wave-transmissive area. The structural bearing area is a carbon material fiber/polyimide resin-based composite material, the wave-transmissive region is a quartz fiber/polyimide resin-based composite material, and the transition area is a chopped carbon material fiber-chopped quartz fiber/polyimide resin-based composite material.
The co-curing integrated forming of the structure bearing area, transition area and wave-transmitting area is realized, which avoids the phenomenon of interface layering, improves the interlayer shear strength, simplifies the preparation process, and reduces production costs.
Smart Images

Figure CN119505531A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of composite materials, and in particular relates to a high temperature resistant structural load bearing-wave transmission integrated composite material and a preparation method thereof. Background Art
[0002] Polyimide is often used as the matrix resin of structural load-bearing materials to reinforce resin-based composite materials in the field of high-temperature load-bearing, and as the matrix resin of wave-transmitting materials to reinforce resin-based composite materials in the field of high-temperature wave-transmitting. With the development of the aerospace field, the materials used in component products are required to have high-temperature resistance, mechanical properties of structural load-bearing, and multifunctional properties of wave-transmitting functions.
[0003] The high temperature resistant structural load-bearing-wave-transparent composite materials in the prior art are usually formed into components by separately molding the high temperature resistant load-bearing structure and the high temperature resistant wave-transparent structure, and then the two components are bonded or riveted together to assemble into a product, which has the disadvantages of long preparation cycle, high production cost, and low reliability. The existing high temperature resistant structural load-bearing-wave-transparent composite materials have serious interface stratification and technical problems such as low interlayer shear strength. Moreover, the curing temperature of polyimide is relatively high. During the preparation of the composite material, the higher the curing temperature of the resin matrix, the greater the interface stress and the more serious the interface stratification phenomenon. The existing preparation method cannot alleviate the interface stratification problem of polyimide-based composite materials.
[0004] Therefore, it is of great significance to provide a high-temperature resistant structural load-bearing-wave-transparent integrated composite material and a preparation method thereof to alleviate the delamination phenomenon in the high-temperature resistant structural load-bearing-wave-transparent integrated composite material and improve the interlaminar shear strength. Summary of the invention
[0005] In view of the above analysis, the present invention aims to provide a high temperature resistant structural load-bearing-wave-transparent integrated composite material and a preparation method thereof, so as to solve at least one of the above technical problems.
[0006] In a first aspect, the present invention provides a high temperature resistant structural load-bearing-wave-transparent integrated composite material, comprising a structural load-bearing area, a transition area and a wave-transparent area connected in sequence, the structural load-bearing area, the transition area and the wave-transparent area are located in the same plane, and the transition area is located between the structural load-bearing area and the wave-transparent area, the structural load-bearing area, the transition area and the wave-transparent area are integrally formed by co-curing, the structural load-bearing area comprises a carbon material fiber / polyimide resin-based composite material, the wave-transparent area comprises a quartz fiber / polyimide resin-based composite material, and the transition area comprises a chopped carbon material fiber-chopped quartz fiber / polyimide resin-based composite material.
[0007] Furthermore, the carbon material fiber in the carbon material fiber / polyimide resin-based composite material includes at least one of carbon fiber, graphite fiber, carbon nanotube fiber, and graphene fiber.
[0008] Furthermore, in the chopped carbon material fibers-chopped quartz fibers / polyimide resin-based composite material, the lengths of the chopped carbon material fibers and the chopped quartz fibers are both 0.5-1.0 mm.
[0009] Furthermore, the thickness of the transition zone is 0.2-1.0 mm.
[0010] Furthermore, the polyimide resin in the carbon material fiber / polyimide resin-based composite material, the quartz fiber / polyimide resin-based composite material and the chopped carbon material fiber-chopped quartz fiber / polyimide resin-based composite material is the same.
[0011] In a second aspect, the present invention provides a method for preparing any high temperature resistant structural load bearing-wave-transmitting integrated composite material as described above, comprising the following steps:
[0012] Step (1), spreading the carbon material fiber / polyimide resin-based prepreg on the mold, so that the carbon material fiber / polyimide resin-based prepreg is surrounded on the surface of the mold to form a ring structure;
[0013] Step (2), paving the quartz fiber / polyimide resin-based prepreg inside the annular structure without contacting the quartz fiber / polyimide resin-based prepreg with the carbon material fiber / polyimide resin-based prepreg;
[0014] Step (3), laying chopped carbon fiber-chopped quartz fiber / polyimide resin-based prepreg film between the carbon fiber / polyimide resin-based prepreg and the quartz fiber / polyimide resin-based prepreg to form a precured structure of quartz fiber / polyimide resin-based prepreg, chopped carbon fiber-chopped quartz fiber / polyimide resin-based prepreg film and carbon fiber / polyimide resin-based prepreg from inside to outside;
[0015] Step (4), co-curing and integrally molding the pre-cured structure to obtain a high temperature resistant structural load-bearing and wave-transmitting integrated composite material.
[0016] Furthermore, the preparation method of the chopped carbon fiber-chopped quartz fiber / polyimide resin-based prepreg film includes:
[0017] Cutting the carbon fiber / polyimide resin-based prepreg and the quartz fiber / polyimide resin-based prepreg into chopped carbon fiber / polyimide resin-based prepreg and chopped quartz fiber / polyimide resin-based prepreg respectively;
[0018] Short-cut carbon fiber / polyimide resin-based prepreg and short-cut quartz fiber / polyimide resin-based prepreg are added into a solvent and mixed to obtain a homogeneous suspension, and the homogeneous suspension is used to prepare a short-cut carbon fiber-short-cut quartz fiber / polyimide resin-based composite film.
[0019] Furthermore, the mass fraction of the polyimide resin in the homogeneous suspension is 30-60%.
[0020] Furthermore, the weight ratio of the chopped carbon fiber / polyimide resin-based prepreg and the chopped quartz fiber / polyimide resin-based prepreg is 0.2:0.8 to 0.8-0.2.
[0021] Further, the solvent includes at least one of N-methylpyrrolidone (NMP), N,N-dimethylacetamide (DMAC), dioxane, methanol and ethanol.
[0022] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:
[0023] (1) The matrix resins in the structural bearing area, transition area and wave-transparent area of the high-temperature resistant structural bearing-wave-transparent integrated composite material of the present invention are all polyimide resins, and the curing temperatures are the same or close, and the transition area can effectively reduce the internal stress caused by high-temperature curing, so that the structural bearing area, transition area and wave-transparent area can be co-cured and integrated into one. In the preparation process, a multifunctional material with high temperature resistance, structural bearing and wave-transparent properties can be formed by one-time curing. The preparation method has the advantages of short preparation cycle, avoiding riveting and glue joint processes, and reducing production costs.
[0024] (2) The transition zone of the present invention includes chopped carbon material fibers consistent with the material of the structural bearing zone and chopped quartz fibers consistent with the material of the wave-transmitting zone, thereby avoiding the risk of interface stratification caused by complete mismatch of interface materials between the structural bearing zone and the wave-transmitting zone, thereby ensuring that there is no stratification defect at the interface between the structural bearing zone and the wave-transmitting zone in the high-temperature resistant structural bearing-wave-transmitting integrated composite material of the present invention.
[0025] (3) The transition zone of the present invention includes short-cut carbon fiber-short-cut quartz fiber / polyimide resin-based composite materials. Without affecting the interface strength, the fiber length is reduced to form a uniformly dispersed mixed fiber, thereby increasing the interface performance; and the interlaminar shear strength of the composite material is greatly improved.
[0026] (4) The thickness of the transition zone of the present invention is 0.2-1.0 mm. The thickness of the transition zone is relatively small, and the effect on the quality of the high-temperature structural load-bearing-wave-transparent integrated composite material can be ignored while avoiding interface delamination of the high-temperature structural load-bearing-wave-transparent integrated composite material.
[0027] (5) The present invention uses polyimide resin as the matrix resin, and the polyimide resin has good high temperature resistance, so that the high temperature resistant structural load-bearing-wave-transparent integrated composite material of the present invention can withstand aerodynamic loads and structural loads at high temperatures (for example, greater than or equal to 350° C.). Moreover, the high temperature resistant structural load-bearing-wave-transparent integrated composite material of the present invention is a multifunctional material that has high temperature resistance, structural load-bearing and wave-transparent properties, and is very suitable for use in aerospace materials.
[0028] Other features and advantages of the present invention will be described in the following description, and part of them will become obvious from the description, or will be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the contents particularly pointed out in the written description and the drawings of the description. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.
[0030] Figure 1 It is a schematic structural diagram of a high temperature resistant structural load bearing-wave transparent integrated composite material according to an embodiment of the present invention.
[0031] Figure 2 This is a CT photo of the high temperature resistant structural load-bearing and wave-transmitting integrated composite material obtained in Example 1 of the present invention.
[0032] Figure 3 This is a CT photo of the integrated composite material obtained in Comparative Example 1.
[0033] Explanation of symbols:
[0034] 100-high temperature resistant structural load-bearing-wave-transparent integrated composite material; 10-structural load-bearing area; 20-transition area; 30-wave-transparent area. DETAILED DESCRIPTION
[0035] Preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of the present invention and are used to explain the principles of the present invention together with the embodiments of the present invention.
[0036] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as commonly understood by technicians in the technical field to which the present invention belongs; the terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present application.
[0037] Reference to "embodiments" in the present invention means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in the present invention may be combined with other embodiments.
[0038] In the present invention, the term "A / B" refers to a composite material formed by A and B. For example, a carbon fiber / polyimide resin matrix composite material refers to a composite material in which carbon fiber is placed in a polyimide resin matrix.
[0039] In the present invention, the term "annular structure" is not limited to a circular ring, and can be an annular structure of any shape, for example, a square annular structure, a triangular annular structure or other irregular annular structures, as long as they are enclosed into an annular structure with a gap in the middle.
[0040] In the present application, unless otherwise specified, the numerical range "ab" means including the end values a, b and any numerical value between a and b.
[0041] If there is no special description, all steps of the present application can be performed sequentially or randomly, preferably sequentially. If there is no special description, the "including" mentioned in the present application means open or closed. For example, the "including" may mean that other components not listed may also be included or only the listed components may be included.
[0042] A specific embodiment of the present invention discloses a high-temperature resistant structural load-bearing-wave-transparent integrated composite material, comprising a structural load-bearing area, a transition area and a wave-transparent area connected in sequence, the structural load-bearing area, the transition area and the wave-transparent area are located in the same plane, and the transition area is located between the structural load-bearing area and the wave-transparent area, and the structural load-bearing area, the transition area and the wave-transparent area are integrally formed by co-curing, the structural load-bearing area comprises a carbon material fiber / polyimide resin-based composite material, the wave-transparent area comprises a quartz fiber / polyimide resin-based composite material, and the transition area comprises a chopped carbon material fiber-chopped quartz fiber / polyimide resin-based composite material.
[0043] See also Figure 1, an embodiment of the present invention provides a high temperature resistant structural load-bearing-wave-transparent integrated composite material 100, and the high temperature resistant structural load-bearing-wave-transparent integrated composite material 100 includes a structural load-bearing area 10, a transition area 20 and a wave-transparent area 30 connected in sequence. The structural load-bearing area 10, the transition area 20 and the wave-transparent area 30 are located on the same plane, and from the inside to the outside, they are the wave-transparent area 30, the transition area 20 and the structural load-bearing area 10. The structural load-bearing area 10, the transition area 20 and the wave-transparent area 30 are integrally formed by co-curing. The structural load-bearing area 10 includes a carbon material fiber / polyimide resin-based composite material, the wave-transparent area 20 includes a quartz fiber / polyimide resin-based composite material, and the transition area 30 includes a chopped carbon material fiber-chopped quartz fiber / polyimide resin-based composite material.
[0044] The carbon material fiber in the carbon material fiber / polyimide resin-based composite material includes but is not limited to at least one of carbon fiber, graphite, carbon nanotube, and graphene. In the present embodiment, the carbon material fiber in the carbon material fiber / polyimide resin-based composite material is carbon fiber. Carbon fiber has the characteristics of light weight, high strength, high rigidity, corrosion resistance, good thermal stability, etc., and is very suitable as a structural bearing area and is used in the materials of aerospace products.
[0045] The thickness of the structural bearing area 10 can be selected according to the actual design load. In this embodiment, the thickness of the structural bearing area 10 is 1 mm.
[0046] If the thickness of the transition zone 20 is too large, the mass of the high temperature resistant structural load-bearing-wave-transparent integrated composite material will be excessively increased; if the thickness of the transition zone 20 is too small, the effect of avoiding the interface delamination between the structural load-bearing area 10 and the wave-transparent area 30 is not obvious. The thickness of the transition zone 20 is preferably, but not limited to, 0.2-1.0 mm. More preferably, the thickness of the transition zone 20 is 0.6-0.8 mm. In this embodiment, the thickness of the transition zone 20 is 0.7 mm.
[0047] The chopped carbon material fibers in the transition zone 20 are carbon material fibers with reduced length obtained by cutting carbon material fibers, and the chopped quartz fibers are quartz fibers with reduced length obtained by cutting quartz fibers. If the fiber length of the chopped carbon material fibers and the chopped quartz fibers in the transition zone 20 is too small, they cannot play a role in enhancing the strength of the interfacial polyimide resin. If the fiber length is too long, the viscosity of the mixed fiber film is too large and it is not easy to disperse, resulting in reduced interfacial performance. The length of the chopped carbon material fibers and the chopped quartz fibers in the chopped carbon material fibers-chopped quartz fibers-polyimide resin composite material is preferably, but not limited to, 0.5-1.0 mm. In this embodiment, the lengths of the chopped carbon material fibers and the chopped quartz fibers in the chopped carbon material fibers-chopped quartz fibers-polyimide resin composite material are both 0.6 mm.
[0048] The thickness of the wave-transmitting area 30 can be designed according to actual needs. In this embodiment, the thickness of the wave-transmitting area 30 is 1 mm.
[0049] The polyimide resin in the carbon fiber / polyimide resin-based composite material, the quartz fiber / polyimide resin-based composite material, and the chopped carbon fiber-chopped quartz fiber / polyimide resin-based composite material preferably has substantially the same curing temperature, so that the structural bearing area 10, the transition area 20, and the wave-transmitting area 30 can be integrally formed by co-curing. More preferably, the polyimide resin in the carbon fiber / polyimide resin-based composite material, the quartz fiber / polyimide resin-based composite material, and the chopped carbon fiber-chopped quartz fiber / polyimide resin-based composite material is the same. In this embodiment, the polyimide resin in the carbon fiber / polyimide resin-based composite material, the quartz fiber / polyimide resin-based composite material, and the chopped carbon fiber-chopped quartz fiber / polyimide resin-based composite material is KH-400N polyimide.
[0050] Compared with the prior art, the high temperature resistant structural load bearing-wave transparent integrated composite material provided by the embodiment of the present invention has the functions of high temperature resistance, structural load bearing and wave transparency, meeting the requirements of aerospace materials having multifunctional properties. The transition zone includes chopped carbon material fibers consistent with the material of the structural load bearing zone, and chopped quartz fibers consistent with the material of the wave transparent zone, so that there is no delamination defect at the interface between the structural load bearing zone and the wave transparent zone in the high temperature resistant structural load bearing-wave transparent integrated composite material of the present invention; moreover, the transition zone can also greatly improve the interlaminar shear strength of the composite material. Polyimide resin is used as the matrix resin, and polyimide resin has good high temperature resistance, so that the high temperature resistant structural load bearing-wave transparent integrated composite material can withstand aerodynamic loads and structural loads under high temperatures (for example, greater than or equal to 350°C), solving the existing
[0051] The embodiment of the present invention also provides a method for preparing the high temperature resistant structural load bearing and wave-transmitting integrated composite material 100 as described above, comprising the following steps:
[0052] Step (1), spreading the carbon material fiber / polyimide resin-based prepreg on the mold, so that the carbon material fiber / polyimide resin-based prepreg is surrounded on the surface of the mold to form a ring structure;
[0053] Step (2), spreading the quartz fiber / polyimide resin-based prepreg inside the annular structure without contacting the quartz fiber / polyimide resin-based prepreg with the carbon material fiber / polyimide resin-based prepreg;
[0054] Step (3), laying chopped carbon fiber-chopped quartz fiber / polyimide resin-based prepreg film between the carbon fiber / polyimide resin-based prepreg and the quartz fiber / polyimide resin-based prepreg to form a precured structure of quartz fiber / polyimide resin-based prepreg, chopped carbon fiber-chopped quartz fiber / polyimide resin-based prepreg film and carbon fiber / polyimide resin-based prepreg from inside to outside;
[0055] Step (4), co-curing and integrally molding the pre-cured structure to obtain a high temperature resistant structural load-bearing and wave-transmitting integrated composite material.
[0056] In step (1), the mass ratio of carbon fiber to polyimide resin in the carbon fiber / polyimide resin-based prepreg can be selected according to actual needs. In this embodiment, the mass ratio of carbon fiber to polyimide resin in the carbon fiber / polyimide resin-based prepreg is 63:37.
[0057] The carbon material fiber / polyimide resin-based prepreg can be selected according to actual conditions. The carbon material fiber can be selected from but not limited to at least one of carbon fiber, carbon nanotube fiber, graphite fiber, and graphene fiber. Preferably, the carbon material fiber / polyimide resin-based prepreg is a carbon fiber-polyimide resin-based prepreg. In the present embodiment, the carbon material fiber / polyimide resin-based prepreg is a T700 carbon fiber KH-400N polyimide prepreg.
[0058] The thickness of the carbon fiber / polyimide resin-based prepreg can be selected according to actual needs. In this embodiment, the thickness of the carbon fiber / polyimide resin-based prepreg is 1 mm.
[0059] In some optional embodiments, before the carbon material fiber / polyimide resin-based prepreg is laid on the mold, the carbon material fiber / polyimide resin-based prepreg is further cut to correspond to the size of the mold.
[0060] In step (2), the thickness of the quartz fiber / polyimide resin-based prepreg can be selected according to actual needs. In this embodiment, the thickness of the quartz fiber / polyimide resin-based prepreg is 1 mm.
[0061] In some optional embodiments, before the quartz fiber / polyimide resin-based prepreg is laid on the chopped carbon material fiber-chopped quartz fiber / polyimide resin-based prepreg film, the quartz fiber / polyimide resin-based prepreg is further cut to correspond to the size of the mold.
[0062] In step (3), the method for preparing the chopped carbon fiber-chopped quartz fiber / polyimide resin-based prepreg film comprises:
[0063] Step (a), cutting the carbon material fiber / polyimide resin-based prepreg and the quartz fiber / polyimide resin-based prepreg into chopped carbon material fiber / polyimide resin-based prepreg and chopped quartz fiber / polyimide resin-based prepreg respectively;
[0064] Step (b), adding chopped carbon fiber / polyimide resin-based prepreg and chopped quartz fiber / polyimide resin-based prepreg into a solvent and blending them to obtain a homogeneous suspension, and using the homogeneous suspension to prepare a chopped carbon fiber-chopped quartz fiber-polyimide resin composite film.
[0065] In step (a), the fiber length of the chopped carbon material fibers in the chopped carbon material fibers / polyimide resin-based prepreg and the chopped quartz fibers in the chopped quartz fibers / polyimide resin-based prepreg is preferably, but not limited to, 0.5-1.0 mm. In this embodiment, the length of the chopped carbon material fibers and the chopped quartz fibers is 0.6 mm.
[0066] In step (b), the solvent is selected according to actual needs, as long as it can dissolve the polyimide in the carbon material fiber / polyimide resin-based prepreg and the quartz fiber / polyimide resin-based prepreg. Preferably, the solvent includes but is not limited to at least one of N-methylpyrrolidone (NMP), N,N-dimethylacetamide (DMAC), dioxane, methanol and ethanol. In this embodiment, the solvent is ethanol.
[0067] If the ratio of chopped carbon fiber / polyimide resin-based prepreg and chopped quartz fiber / polyimide resin-based prepreg is too high or too low, the transition zone 20 does not have the fusion effect of the two, which will cause the structural bearing area 10 and the wave-transmitting area 30 to be delaminated. The weight ratio of chopped carbon fiber / polyimide resin-based prepreg and chopped quartz fiber / polyimide resin-based prepreg is preferably, but not limited to, 0.2:0.8 to 0.8-0.2. More preferably, the weight ratio of chopped carbon fiber / polyimide resin-based prepreg and chopped quartz fiber / polyimide resin-based prepreg is 0.5:0.5.
[0068] If the polyimide resin content is too high, the system viscosity is high, which is not conducive to the dispersion of short-cut fibers; if the polyimide resin content is too low, the solvent content is high, and too much residue is left inside during the later composite material molding process, which easily generates pores and causes defects. The mass fraction of the polyimide resin in the homogeneous suspension is preferably, but not limited to, 30-60%.
[0069] The thickness of the chopped carbon fiber-chopped quartz fiber-polyimide resin composite film can be selected according to actual needs. Preferably, the thickness of the chopped carbon fiber-chopped quartz fiber-polyimide resin composite film is 0.1-0.2 mm. In this embodiment, the thickness of the chopped carbon fiber-chopped quartz fiber-polyimide resin composite film is 0.2 mm.
[0070] In step (4), in some embodiments, the pre-cured structure is co-cured and integrated into one piece, including: molding the pre-cured structure; preparing the composite material by a compression molding process, wherein the curing temperature is selected according to the type of polyimide resin, and the curing time is 2-4 hours; cooling to room temperature after curing, and demolding to obtain a high temperature resistant structural load-bearing and wave-transparent integrated composite material.
[0071] The preparation method of the high temperature resistant structural load bearing-wave transparent integrated composite material provided by the above embodiment of the present invention can form a multifunctional material with high temperature resistance, structural load bearing and wave transparency through one-time curing. The preparation method has the advantages of short preparation cycle, avoiding riveting and gluing process, and reducing production cost. The transition zone includes chopped carbon material fibers consistent with the material of the structural load bearing zone, and chopped quartz fibers consistent with the material of the wave transparent zone, so that there is no delamination defect at the interface between the structural load bearing zone and the wave transparent zone in the high temperature resistant structural load bearing-wave transparent integrated composite material obtained by the preparation method of the present invention; moreover, the transition zone can also greatly improve the interlaminar shear strength of the composite material. In the preparation method, polyimide resin is used as the matrix resin, and the polyimide resin has good high temperature resistance, so that the high temperature resistant structural load bearing-wave transparent integrated composite material can withstand aerodynamic loads and structural loads at high temperatures (for example, greater than or equal to 350°C).
[0072] Embodiments of the present invention also provide applications of the high-temperature resistant structural load-bearing-wave-transparent integrated composite material as described in any of the above embodiments or the high-temperature resistant structural load-bearing-wave-transparent integrated composite material obtained by the preparation method of any of the above embodiments in aerospace materials.
[0073] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments and comparative examples.
[0074] Embodiment 1:
[0075] 1 mm T700 carbon fiber / KH-400N polyimide resin-based prepreg and 1 mm quartz fiber / KH-400N polyimide resin-based prepreg were cut as a high-temperature resistant bearing layer and a high-temperature resistant wave-transparent area waiting for laying, respectively. The T700 carbon fiber / KH-400N polyimide resin-based and quartz fiber / KH-400N polyimide resin-based prepregs were cut into short-cut T700 carbon fiber / KH-400N polyimide resin-based and short-cut quartz fiber / KH-400N polyimide resin-based prepregs with a knife roller having a length of 0.5 mm, and then dissolved in an ethanol solvent at a weight ratio of 0.5:0.5. After dissolution, a film with a thickness of 0.2 mm was prepared using a film machine. 1mm T700 carbon fiber / KH-400N polyimide prepreg is laid into the mold, and then two layers of 0.2mm transition zone adhesive film and 1mm quartz fiber / KH-400N polyimide resin-based prepreg are stacked and placed. The molds are closed and the composite material is prepared by a compression molding process. The curing temperature is 380°C and the curing time is 3h. After curing, it is cooled to room temperature and demolded to obtain a high-temperature resistant structural load-bearing and wave-transmitting integrated composite material.
[0076] Embodiment 2:
[0077] 1 mm T700 carbon fiber / KH-400N polyimide resin-based prepreg and 1 mm quartz fiber / KH-400N polyimide resin-based prepreg were cut as a high-temperature resistant bearing layer and a high-temperature resistant wave-transparent area waiting for laying, respectively. The T700 carbon fiber / KH-400N polyimide resin-based prepreg and the quartz fiber / KH-400N polyimide resin-based prepreg were cut into short-cut T700 carbon fiber / KH-400N polyimide resin-based and short-cut quartz fiber / KH-400N polyimide resin-based prepregs with a length of 0.2 mm by a knife roller, and then dissolved in an ethanol solvent at a weight ratio of 0.5:0.5. After dissolution, a film with a thickness of 0.2 mm was prepared by a film machine. 1 mm T700 carbon fiber / KH-400N polyimide resin-based prepreg is laid into the mold, and then three layers of 0.2 mm transition zone adhesive film and 1 mm quartz fiber / KH-400N polyimide resin-based prepreg are stacked and placed. The molds are closed and the composite material is prepared by a compression molding process. The curing temperature is 380 ° C and the curing time is 3 h. After curing, it is cooled to room temperature and demolded to obtain a high temperature resistant structural load-bearing and wave-transmitting integrated composite material.
[0078] Embodiment 3:
[0079] 1 mm T700 carbon fiber / KH-400N polyimide resin-based prepreg and 1 mm quartz fiber / KH-400N polyimide resin-based prepreg were cut as a high-temperature resistant bearing layer and a high-temperature resistant wave-transparent area waiting for laying, respectively. The T700 carbon fiber / KH-400N polyimide resin-based prepreg and the quartz fiber / KH-400N polyimide resin-based prepreg were cut into short-cut T700 carbon fiber / KH-400N polyimide resin-based and short-cut quartz fiber / KH-400N polyimide resin-based prepregs with a length of 1.0 mm by a knife roller, and then dissolved in an ethanol solvent at a weight ratio of 0.5:0.5. After dissolution, a film with a thickness of 0.2 mm was prepared by a film machine. 1mm T700 carbon fiber / KH-400N polyimide resin-based prepreg is laid into the mold, and then four layers of 0.2mm transition zone adhesive film and 1mm quartz fiber / KH-400N polyimide resin-based prepreg are stacked and placed. The mold is closed and the composite material is prepared by a compression molding process. The curing temperature is 380°C and the curing time is 3h. After curing, it is cooled to room temperature and demolded to obtain a high-temperature resistant structural load-bearing and wave-transmitting integrated composite material.
[0080] Embodiment 4:
[0081] 1 mm T700 carbon fiber / KH-400N polyimide resin-based prepreg and 1 mm quartz fiber / KH-400N polyimide resin-based prepreg were cut as a high-temperature resistant bearing layer and a high-temperature resistant wave-transparent area waiting for laying, respectively. The T700 carbon fiber / KH-400N polyimide resin-based prepreg and the quartz fiber / KH-400N polyimide resin-based prepreg were cut into short-cut T700 carbon fiber / KH-400N polyimide resin-based and short-cut quartz fiber / KH-400N polyimide resin-based prepregs with a length of 1.0 mm by a knife roller, and then dissolved in an ethanol solvent at a weight ratio of 0.5:0.5. After dissolution, a film with a thickness of 0.2 mm was prepared by a film machine. 1mm T700 carbon fiber / KH-400N polyimide resin-based prepreg is laid into the mold, and then five layers of 0.2mm transition zone adhesive film and 1mm quartz fiber / KH-400N polyimide resin-based prepreg are stacked and placed. The mold is closed and the composite material is prepared by a compression molding process. The curing temperature is 380°C and the curing time is 3h. After curing, it is cooled to room temperature and demolded to obtain a high-temperature resistant structural load-bearing and wave-transmitting integrated composite material.
[0082] Comparative Example 1:
[0083] 1mm T700 carbon fiber / KH-400N polyimide resin-based prepreg and 1mm quartz fiber / KH-400N polyimide resin-based prepreg were cut and used as high temperature resistant bearing layer and high temperature resistant wave-transparent area to be laid. 1mm T700 carbon fiber / KH-400N polyimide resin-based prepreg was laid into the mold, followed by 1mm quartz fiber / KH-400N polyimide resin-based prepreg, and the mold was closed. The composite material was prepared by compression molding process, with a curing temperature of 380°C and a curing time of 3h. After curing, it was cooled to room temperature and demolded to obtain an integrated composite material.
[0084] Comparative Example 2:
[0085] 1mm T700 carbon fiber / KH-400N polyimide resin-based prepreg was laid into the mold, followed by the 0.6mm transition zone of alternately laid T700 carbon fiber / KH-400N polyimide resin-based and quartz fiber cloth / KH-400N polyimide resin-based prepreg, and 1mm quartz fiber / KH-400N polyimide resin-based prepreg was placed. The mold was closed and the composite material was prepared by compression molding process. The curing temperature was 380℃ and the curing time was 3h. After curing, it was cooled to room temperature and demolded to obtain an integrated composite material. After testing, the composite material CT showed that there was a slight delamination defect between the high temperature bearing layer and the high temperature wave-transparent area, and the interlaminar shear strength of the composite material was tested. The test results are shown in Table 1.
[0086] The high temperature resistant structural load-bearing and wave-transmitting integrated composite materials obtained in Examples 1-4 and the integrated composite materials obtained in Comparative Examples 1-2 were subjected to CT testing and interlaminar shear strength testing to obtain the delamination between the structural load-bearing area and the wave-transmitting area and the interlaminar shear strength. The test results are detailed in Table 1:
[0087] Table 1 Composite material properties
[0088]
[0089] It can be seen from the test results in Table 1 that there are no delamination defects between the structural bearing area, the wave-transparent area and the transition area in the high-temperature resistant structural bearing-wave-transparent integrated composite materials of Examples 1-4, and the internal quality is intact. There is a large continuous delamination defect between the structural bearing area and the wave-transparent area of Comparative Example 1, and there is a slight delamination defect between the structural bearing area and the wave-transparent area of Comparative Example 2. It can also be seen that the room temperature and 400°C high temperature interlaminar shear strength of the high-temperature resistant structural bearing-wave-transparent integrated composite materials of Examples 1-4 are greater than the interlaminar shear strength of the integrated composite materials of Comparative Examples 1 and 2. The comparison results of Examples 1-4 and Comparative Example 1-2 show that the high-temperature resistant structural bearing-wave-transparent integrated composite materials obtained in the embodiments of the present invention include a transition zone of chopped carbon material fiber-chopped quartz fiber-polyimide resin composite materials, which can well avoid the interlaminar interface delamination defects of the composite material and improve the interlaminar shear strength of the composite material.
[0090] From the comparison of the results of Examples 1-4 in Table 1, it can be seen that the interlaminar shear strength in Example 2 is the largest, indicating that when the thickness of the transition zone is 0.6 mm, the interlaminar shear strength of the obtained high-temperature resistant structural load-bearing-wave-transparent integrated composite material is higher than the interlaminar shear strength of the composite material when the thickness is 0.4 mm, 0.8 mm and 1.0 mm.
[0091] See also Figure 2 , which is a CT photo of the high temperature resistant structural load-bearing-wave-transmitting integrated composite material obtained in Example 1, Figure 2 It can be seen that there is no delamination defect between the structural bearing area, wave-transmitting area and transition area, and the internal quality is intact. Figure 3 , is a CT photo of the integrated composite material obtained in Comparative Example 1, Figure 3 It can be seen that there is a large continuous delamination defect between the structural bearing area and the wave-transmitting area, which further illustrates that the transition zone of the high-temperature resistant structural bearing-wave-transmitting integrated composite material obtained in the embodiment of the present invention can well avoid the delamination defect of the interlayer interface of the composite material and improve the internal quality of the high-temperature resistant structural bearing-wave-transmitting integrated composite material.
[0092] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A high temperature resistant structural load-bearing and wave-transmitting integrated composite material, characterized in that: The invention comprises a structure bearing area, a transition area and a wave-transmitting area connected in sequence, wherein the structure bearing area, the transition area and the wave-transmitting area are located in the same plane, and the transition area is located between the structure bearing area and the wave-transmitting area. The structure bearing area, the transition area and the wave-transmitting area are integrally formed by co-curing. The structure bearing area comprises a carbon material fiber / polyimide resin-based composite material, the wave-transmitting area comprises a quartz fiber / polyimide resin-based composite material, and the transition area comprises a chopped carbon material fiber-chopped quartz fiber / polyimide resin-based composite material.
2. The high temperature resistant structural load bearing and wave transmission integrated composite material according to claim 1, characterized in that: The carbon material fiber in the carbon material fiber / polyimide resin-based composite material includes at least one of carbon fiber, graphite fiber, carbon nanotube fiber and graphene fiber.
3. The high temperature resistant structural load bearing and wave transmission integrated composite material according to claim 1 or 2, characterized in that: The lengths of the chopped carbon material fibers and the chopped quartz fibers in the chopped carbon material fibers-chopped quartz fibers / polyimide resin-based composite material are both 0.5-1.0 mm.
4. The high temperature resistant structural load bearing and wave transmission integrated composite material according to claim 1 or 2, characterized in that: The thickness of the transition zone is 0.2-1.0 mm.
5. The high temperature resistant structural load bearing and wave transmission integrated composite material according to claim 1 or 2, characterized in that: The polyimide resin in the carbon material fiber / polyimide resin-based composite material, the quartz fiber / polyimide resin-based composite material and the chopped carbon material fiber-chopped quartz fiber / polyimide resin-based composite material is the same.
6. A method for preparing the high temperature resistant structural load bearing and wave transmission integrated composite material according to any one of claims 1 to 5, characterized in that: The following steps are involved: Step (1), spreading the carbon material fiber / polyimide resin-based prepreg on the mold, so that the carbon material fiber / polyimide resin-based prepreg forms a ring-shaped structure area on the surface of the mold; Step (2), spreading the quartz fiber / polyimide resin-based prepreg inside the annular structure region without contacting the quartz fiber / polyimide resin-based prepreg with the carbon material fiber / polyimide resin-based prepreg; Step (3), laying chopped carbon fiber-chopped quartz fiber / polyimide resin-based prepreg film between the carbon fiber / polyimide resin-based prepreg and the quartz fiber / polyimide resin-based prepreg to form a precured structure of quartz fiber / polyimide resin-based prepreg, chopped carbon fiber-chopped quartz fiber / polyimide resin-based prepreg film and carbon fiber / polyimide resin-based prepreg from inside to outside; Step (4), co-curing and integrally molding the pre-cured structure to obtain a high temperature resistant structural load-bearing and wave-transmitting integrated composite material.
7. The method for preparing the high temperature resistant structural load bearing and wave transmission integrated composite material according to claim 6, characterized in that: The preparation method of the chopped carbon fiber-chopped quartz fiber / polyimide resin-based prepreg film comprises: Cutting the carbon fiber / polyimide resin-based prepreg and the quartz fiber / polyimide resin-based prepreg into chopped carbon fiber / polyimide resin-based prepreg and chopped quartz fiber / polyimide resin-based prepreg respectively; The chopped carbon fiber / polyimide resin-based prepreg and the chopped quartz fiber / polyimide resin-based prepreg are added into a solvent and mixed to obtain a homogeneous suspension, and the homogeneous suspension is used to prepare a chopped carbon fiber-chopped quartz fiber / polyimide resin-based composite material film.
8. The method for preparing the high temperature resistant structural load bearing and wave transmission integrated composite material according to claim 7, characterized in that: The mass fraction of the polyimide resin in the homogeneous suspension is 30-60%.
9. The method for preparing the high temperature resistant structural load bearing and wave transmission integrated composite material according to claim 7, characterized in that: The weight ratio of the chopped carbon fiber / polyimide resin-based prepreg and the chopped quartz fiber / polyimide resin-based prepreg is 0.2:0.8 to 0.8-0.
2.
10. The method for preparing the high temperature resistant structural load bearing and wave transmission integrated composite material according to any one of claims 7 to 9, characterized in that: The solvent includes at least one of N-methylpyrrolidone (NMP), N,N-dimethylacetamide (DMAC), dioxane, methanol and ethanol.